The Use of Traditional And Non-Traditional Methods In EFL Classroom - Nazarova, Yorqinoy (Indonesian Journal Publisher, 2025)
This article explores the use of traditional and non-traditional methods in English as a Foreign Language (EFL) classrooms, highlighting their strengths, challenges, and applications. Traditional methods, such as the grammar translation and audiolingual approaches, offer structured learning environments with a focus on grammar and vocabulary but often lack opportunities for communicative skill development. In contrast, non-traditional methods, including Communicative Language Teaching (CLT), technology-enhanced approaches prioritize learner engagement, creativity, and practical language use. The article emphasizes the importance of integrating both approaches to cater to diverse learner needs, combining the systematic foundation of traditional methods with the dynamism of non-traditional techniques. A balanced methodology ensures a comprehensive and effective language learning experience.